Interventions for Improving Reading Comprehension in Children with ASD: A Systematic Review - Raúl Tárraga-Mínguez; Irene Gómez-Marí; Pilar Sanz-Cervera (Behavioral Sciences, 2020)
Children with autism spectrum disorder (ASD) often have comorbid learning difficulties in reading comprehension, an essential skill in accessing any area of the curriculum. The aim of this systematic review is to analyze the effectiveness of reading comprehension interventions in students with ASD. We conducted a search for scientific articles published from 2000 to 2019 using the keyword “autis*” in combination with the terms “reading comprehension” and “intervention” or “instruction” in Psyc Info and Scopus databases. After applying inclusion and exclusion criteria, a total of 25 studies were selected. The content analysis of these studies shows that when specific interventions are carried out, students with ASD are able to take advantage of the instruction they receive and compensate for difficulties. Understanding inferences and the main idea of the text are the most common reading comprehension topics, and direct instruction is the most widely-used intervention method in the reviewed studies. Nonetheless, it must be kept in mind that some of the reviews do not specify which sub-processes are addressed in the intervention. Future work should include this aspect, consider the importance of the interventions being implemented by teachers, and take specific aspects of ICT into account that can contribute to improving reading comprehension.